2015
DOI: 10.1158/0008-5472.can-15-0159
|View full text |Cite
|
Sign up to set email alerts
|

Affinity-Tuned ErbB2 or EGFR Chimeric Antigen Receptor T Cells Exhibit an Increased Therapeutic Index against Tumors in Mice

Abstract: Target-mediated toxicity is a major limitation in the development of chimeric antigen T cell receptors (CAR) for adoptive cell therapy of solid tumors. In this study, we developed a strategy to adjust the affinities of the scFv component of CAR to discriminate tumors overexpressing the target from normal tissues which express it at physiologic levels. A CAR-expressing T cell panel was generated with target antigen affinities varying over three orders of magnitude. High-affinity cells recognized target expresse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
454
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(478 citation statements)
references
References 39 publications
22
454
2
Order By: Relevance
“…EGFR expression has been observed in both epithelium-derived malignancies and most epithelial cells, raising great concerns in the target-mediated toxicity on EGFR-expressing normal tissues. However, the lower affinity of CAR molecule with EGFR antigen may discriminate the damage activities between normal cells with relatively lower level expression of EGFR and tumors with higher expression (Caruso et al, 2015;Chmielewski et al, 2014;Liu et al, 2015). In this study, tolerable and controllable EGFR targeting-related toxicities were just observed in 11 NSCLC cases as shown in Table 2, implying an appropriate affinity of EGFR-CAR epitope we adopted.…”
Section: Discussionmentioning
confidence: 77%
“…EGFR expression has been observed in both epithelium-derived malignancies and most epithelial cells, raising great concerns in the target-mediated toxicity on EGFR-expressing normal tissues. However, the lower affinity of CAR molecule with EGFR antigen may discriminate the damage activities between normal cells with relatively lower level expression of EGFR and tumors with higher expression (Caruso et al, 2015;Chmielewski et al, 2014;Liu et al, 2015). In this study, tolerable and controllable EGFR targeting-related toxicities were just observed in 11 NSCLC cases as shown in Table 2, implying an appropriate affinity of EGFR-CAR epitope we adopted.…”
Section: Discussionmentioning
confidence: 77%
“…40). Notable examples are provided by recent reports of chimeric antigen receptor (CAR) T cells engineered to present scFv modules spanning a range of affinities for the target antigen (41,42). These studies demonstrate that scFvs with reduced affinities had increased selectivity for solid tumors, relative to normal cells, due to the requirement for higher surface density of target antigens to support productive engagement, a state often afforded by the targeted tumor cells.…”
Section: Mypppymentioning
confidence: 99%
“…These studies demonstrate that scFvs with reduced affinities had increased selectivity for solid tumors, relative to normal cells, due to the requirement for higher surface density of target antigens to support productive engagement, a state often afforded by the targeted tumor cells. For example, CAR T cells bearing scFvs derived from nimotuxumab, but not cetuximab (43), effectively discriminated between malignant cells and nonmalignant cells based on its ∼10-fold poorer K d for EGFR, which is expressed at significantly higher levels on the malignant cells (41). Similar studies, which examined scFvs against EGFR (derived from the C10 anti-EGFR antibody) (44) and ErbB2 (derived from the 4D5 trastuzumab antibody) (45) with K d s spanning ∼2-3 orders of magnitude, have reinforced this concept.…”
Section: Mypppymentioning
confidence: 99%
“…This novel receptor produces synergistic enhancement of effector functions when encountering two antigens and preserves cytolytic ability upon the loss of one target (Grada et al, 2013). In addition, fine-tuning CAR-T cell affinities may increase their therapeutic index, as low-affinity CAR-T cells appear capable of discriminating tumor cells with high EGFR or Her2 expression from tumors with low expression (Caruso et al, 2015;Liu et al, 2015).…”
Section: Increasing the Safety Index Of Carsmentioning
confidence: 99%